Dynamic Compartmentalization of Peptide–Oligonucleotide Conjugates with Reversible Nanovesicle–Microdroplet Phase Transition Behaviors - Wang, Bin; Fang, Honglong; Zhu, Weiping; Xu, Yufang; Yang, Yangyang; Qian, Xuhong (ACS applied materials & interfaces, 2022)
Developing artificial microsystems based on liquid–liquid phase separation (LLPS) to mimic cellular dynamic compartmentalization has gained increasing attention. However, limitations including complicated components and laborious fabrication techniques have hindered their development. Herein, we describe a new single-component dynamic compartmentalization system using peptide–oligonucleotide conjugates (POCs) produced from short elastin-like polypeptides (sELPs) and oligonucleotides (ONs), which can perform thermoreversible phase transition between a nanovesicle and a microdroplet. The phase transition of sELP–ONs is thoroughly investigated, of which the transition temperature can be controlled by concentration, length of sELPs and ONs, base sequences, and salt. Moreover, the sELP–ON microcompartment can enrich a variety of functional molecules including small molecules, polysaccharides, proteins, and nucleic acids. Two sELP–ON compartments are used as nano- and microreactors for enzymatic reactions, separately, in which chemical activities are successfully regulated under different-scaled confinement effects, demonstrating their broad potential application in matter exchange and artificial cells.